Canaanean Blade Knapping Waste Pit from Fazael 4, Israel. (3rd July 2017) - Zutovski, Katia; Bar, Shay
ABSTRACT: A recently excavated Early Bronze Age IB Canaanean blade knapping pit, located at Fazael 4, Israel, is presented. Following a detailed analysis of the waste characteristics we suggest a reconstruction of the chaîne opératoire of the Canaanean blade production at the site. We further discuss the evident variability within the regional Canaanean industry, in view of the technological conservatism found at the Fazael 4 site; the distribution trajectories and the nature of trade or exchange among Canaanean blade workshops and "consumer sites"; and the extent of independence versus elite control over specialized workshops during the Early Bronze Age. To date, studies of only a few sites containing Canaanean industry knapping waste have been published, emphasizing the importance of this site. The Fazael 4 waste pit analysis offers insights into the last highly complex and sophisticated flint technology of the southern Levant.